Shake'n'sense: reducing interference for overlapping structured light depth cameras - Butler, Alex; Izadi, Shahram; Hilliges, Otmar; Molyneaux, David; Hodges, Steve; Kim, David (Proceedings of the 2012 ACM annual conference on Human Factors in Computing Systems, 2012)
We present a novel yet simple technique that mitigates the interference caused when multiple structured light depth cameras point at the same part of a scene. The technique is particularly useful for Kinect, where the structured light source is not modulated. Our technique requires only mechanical augmentation of the Kinect, without any need to modify the internal electronics, firmware or associated host software. It is therefore simple to replicate. We show qualitative and quantitative results highlighting the improvements made to interfering Kinect depth signals. The camera frame rate is not compromised, which is a problem in approaches that modulate the structured light source. Our technique is non-destructive and does not impact depth values or geometry. We discuss uses for our technique, in particular within instrumented rooms that require simultaneous use of multiple overlapping fixed Kinect cameras to support whole room interactions.